Parent's Level of Stress on Children's Online Classes during the COVID-19Pandemic - Nurrosyida, Kartika; Firmanto, Neissya Nastiti; Fayanshah, Irda Bella Ajeng; Sulistyawati, Sri Wijayanti (Journal of Community Medicine and Public Health Research, 2022)
The Covid-19 pandemic is affecting people's lives. One of the sectors hampered by the pandemic is education. During the Coronavirus Disease (Covid-19) Emergency, the teaching and learning process must be replaced by online methods. The role of mothers is very important in ensuring that children's learning targets are achieved during distance learning. This can cause stress conditions for the mother. This study aimed to determine the perceptions and various problems that occurred in mothers with children aged 7-15 years old who attended online schools during the Covid-19 pandemic. This was a descriptive study by distributing questionnaires via google form with 67 respondents. Based on the results, the majority of respondents were 35-45 years old (49.3%). Over 85.6% of respondents accompanied their children in online learning activities during the pandemic. The majority of respondents experienced an increase in emotions (70.1%) and felt stressful when accompanying online school children during the pandemic (62.7%). As many as 40% of respondents felt a moderate level of stress. There were 27 mothers (40%) who had difficulty assisting their children in online schooling and 24 mothers (36%) felt that their professional job was abandoned while their children were having online school.